Communicative language skills: a comparative analysis of duolingo and memrise applications for language learning - SILVA, Cláudio Vitor Corrêa (2024)
The main objective of this study is to analyze the use of mobile applications for and learning English, focusing on the Duolingo and Memrise applications. The methodology of this study consists of a qualitative and exploratory investigation based on bibliographic sources. The research approach is qualitative, exploratory in nature, describing the methods and strategies used by the apps to promote English learning. As general objectives, this study highlights some aspects that involve language learning through the use of technological resources, considering the importance of integrating the language skills for the development of students' communicative abilities, a comparison is made between two mobile apps that were created to help individuals learn English as an additional language: Duolingo and Memrise. To achieve these objectives, the article is based on theoretical contributions from authors such as Harmer (2007, 2010); Brown (2001, 2007); Larsen-Freeman (2011, 2013); Mübert and Pereira (2011); Moran (2015); Barbosa (2020); Paiva (2017) and other researchers who have dedicated themselves intensively to the study of this area. After the exploratory bibliographical research, the two apps in question were analyzed, and possible ways of improving English learning through mobile apps were also identified, such as gamification, personalized feedback, the use of voice recognition technologies, and adaptive approaches to the students' learning pace.